Disability and Comorbidity of Mood Disorders and Anxiety Disorders With Diabetes and Hypertension: Evidences From the China Mental Health Survey and Chronic Disease Surveillance in China - Hu, Yuanyuan; Huang, Yueqin; Wang, Limin; Liu, Zhaorui; Wang, Linhong; Yan, Jie; Zhang, Mei; Lv, Ping; Guan, Yunqi; Ma, Chao; Huang, Zhengjing; Zhang, Tingting; et al. (Frontiers in Psychiatry, 2022)
Background: The China Mental Health Survey was carried out using the same sampling frame with the China Chronic Diseases and Risk Factors Surveillance. This paper explores the relationship between the disability and the comorbidity of mood disorders and anxiety disorders with diabetes and hypertension. Methods: A large-scale nationally representative sample with both mental disorders and chronic diseases was collected from 157 Disease Surveillance Points in 31 provinces across China. Face-to-face interviews were conducted by trained lay interviewers to make diagnoses of mood disorders and anxiety disorders using the Composite International Diagnostic Interview. Diabetes and hypertension were diagnosed from self-report and blood examination or body measurement. Sampling design weights, non-response adjustment weights, and post-stratification adjustment weights were applied during the analyses of comorbidity and disability. Results: Totally 15000 respondents had information of mental disorders and physical diseases. In the patients with mood disorders or anxiety disorders, the weighted prevalence rates of diabetes or hypertension were not higher than those in persons without the above mental disorders, but the weighed disability rates increased when having the comorbidity of hypertension (P<0.05). The severity of disability was higher among patients with comorbidity of diabetes and anxiety disorders, or hypertension and mood disorders, compared with that among patients without the physical comorbidity (P<0.05). After adjusted by age, gender and education, patients with comorbidity of mental disorders and physical disorders had the highest disability, followed by the patients with mental disorders only, and physical diseases only. Conclusions: The disability of mood disorders and anxiety disorders comorbid with diabetes and hypertension are more serious than that of any single disease. The relationship of mental and physical diseases is worth exploring in depth for comprehensive and integrated intervention to decrease the disability.